Factors contributing towards the effectiveness of personal protective equipment (PPE) among the oil palm plantation workers / Ahmad Salim Awang - Awang, Ahmad Salim (Faculty of Plantation and Agrotechnology, 2015)
One of the sources that may contribute to an injury at the workplace is a failure to use personal protective equipment (PPE). The purpose of this research is to identify factors contributing towards the effectiveness of PPE among the oil palm plantation workers. This research is aimed to measure the relationship between selected factors and the effectiveness of PPE. Apart from that, the research also determines the most dominant factor that influences the effectiveness of PPE. Based on the previous literatures, Knowledge, Awareness, Attitude and Subjective Norms were treated as independent variables. Whereby, the effectiveness of PPE becomes the dependent variable. Results of this research indicated that four factors namely Knowledge, Awareness, Attitude and Subjective Norms conclude as independent variable and the effectiveness of PPE as dependent variable. From the regression analysis, the knowledge, awareness and attitude have a significant relationship with the effectiveness of PPE as p < 0.05. However, subjective norms indicated no significant relationship with the effectiveness of PPE. Through stepwise regression analysis, the most dominant factor goes to the dimension of awareness, followed by knowledge and attitude.